Exploring The Implementation of the Merdeka Curriculum: A Case Study of Integrated Science Teaching Materials with ESD and Ethnoscience - Puspita, Gita Nurul; Widodo, Ari; Sriyati, Siti (IJIS Edu : Indonesian Journal of Integrated Science Education, 2024)
This study analyzes the science teaching materials integrated with ESD and Ethnoscience based on teachers' teaching experiences and educational qualifications. This case study research involved six junior high school science teachers in Cimahi City who participated voluntarily in a teacher training program. Data collection techniques in this research used observation, in-depth interviews, and documentation. The data analysis employed a descriptive narrative approach by reducing data, presenting data, and drawing conclusions.  Then, triangulation is also performed for data validation. Based on the research findings, teaching materials prepared by novice teachers with less than five years of teaching experience tend to be textbook-oriented, and the language used still needs to be suitable for the cognitive level of junior high school students. However, the materials they prepared have an attractive appearance. Meanwhile, experienced teachers elaborate and provide contextual examples, using easily understandable language and incorporating tables or graphs to enhance students' literacy and numeracy skills. Out of the six teachers, four have a Biology/ Biology Education background, and two have qualifications in Physics Education at the bachelor's level. Teachers choose teaching materials that align with their educational background because they feel more confident in delivering scientific concepts. Through this research, it is described that teachers still tend to develop teaching materials based on the 2013 curriculum, whereas, at present, the preparation of teaching materials should be aligned with the principles of the Merdeka curriculum.